2016
DOI: 10.1371/journal.pone.0154502
|View full text |Cite
|
Sign up to set email alerts
|

Joint Association of Screen Time and Physical Activity with Cardiometabolic Risk Factors in a National Sample of Iranian Adolescents: The CASPIANIII Study

Abstract: Metabolic syndrome (MetS) and its contributing factors are considered important health problems in the pediatric age group. This study was designed to assess the joint association of ST and PA with cardiometabolic risk factors among Iranian adolescents. A representative sample of 5625 (50.2% boys) school students with a mean age of 14.73 (SD: 2.41) were selected through multistage random cluster sampling method from urban and rural areas of 27 provinces in Iran. ST and PA were assessed by self-administered val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
2
26
0
1
Order By: Relevance
“…In primary school students, inadequate nutrition and malnutrition problems, such as not having the habit of eating breakfast every day [5] , consuming fast food at least once a day and skipping meals are frequently observed [1] , [3] , [6] . The ratio of physical activity and healthy nutrition [7] for children who spend most of their time in front of a television and/or computer is also low [8] . It is found that as the daily time children spend in front of a computer increases, their BMI (Body Mass Index) also increases; however, as the daily time they spend on physical activity increases, the value of BMI decreases [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In primary school students, inadequate nutrition and malnutrition problems, such as not having the habit of eating breakfast every day [5] , consuming fast food at least once a day and skipping meals are frequently observed [1] , [3] , [6] . The ratio of physical activity and healthy nutrition [7] for children who spend most of their time in front of a television and/or computer is also low [8] . It is found that as the daily time children spend in front of a computer increases, their BMI (Body Mass Index) also increases; however, as the daily time they spend on physical activity increases, the value of BMI decreases [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of physical activity and healthy nutrition [7] for children who spend most of their time in front of a television and/or computer is also low [8] . It is found that as the daily time children spend in front of a computer increases, their BMI (Body Mass Index) also increases; however, as the daily time they spend on physical activity increases, the value of BMI decreases [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiometabolic risk factors are clusters of various factors such as tobacco use, (hypertension, dyslipidaemia, low physical activity, high fasting plasma glucose and high body mass index (BMI) (Cardiometabolic Risk Working Group, 2011). Behavioural risk factors such as tobacco use, insufficient physical activity, unhealthy diet and excessive alcohol consumption typically cluster together (Cardiometabolic Risk Working Group, 2011;Zimmet et al, 2007) to contribute to the development of various CVDs and CMDs such as hypertension, diabetes, dyslipidemia and overweight and obesity (Forket et al, 2016;Hazree et al, 2014;Heshmat et al, 2016;Nkeh-Chungag, Sekokotla, Rusike, Namugowa, & Iputo, 2015;Odunaiya, Grimmer, & Louw, 2015). Consequently, these diseases confers a higher cost to manage and treat CMDs in the future (Institute of Public Health, 2011;Mathers, & Loncar, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…P hysical activity is important to the overall health and well-being of everyone, including all school-age children. The benefits of physical activity are well-documented and involve the mitigation of many health risks, including those for developing Type 2 diabetes (Costanian, Bennett, Hwalla, Assaad, & Sibai, 2014;Rottensteiner et al, 2014), high blood pressure and high blood cholesterol (Carpio-Rivera, Moncada-Jiménez, Salazar-Rojas, & Solera-Herrera, 2016;Heshmat et al, 2016). Physical activity also contributes to the building and maintenance of healthy bones and muscles (Sioen et al, 2015), to improve positive mental health (Hilmn, Erikon, & Kramer, 2008;Nguyen -Michel, Unger, Hamilton, & Spruijt-Metz, 2006;Wang et al, 2010), and health-related physical fitness (HRPF) (De Baere, Philippaert, De Martelaer, & Lefevre, 2016;Malacko & Pejčić, 2009).…”
Section: Introductionmentioning
confidence: 99%